Pancasila, The Living Staatsfundamentalnorm Of The Indonesian Nationstate: The Norms, The Institutions, And The Performancel - Saefrudin Bahar (Jurnal Ketahanan Nasional, 2009)
It must be assumed, that having frequently failed for cen- turies in their fights for independence, both in local military confrontations and in the political movements, the Indone- sian leaders heartily welcomed the opportunity to gain their independence at the end of the Second World War. In mid 1945, facing impending defeat against the Allies, Japan's Southern Military Theater Command headquarter in Saigon gave the green light to Mr Soekarno, Mr Mohammad Hatta and Dr Radjiman Wedyodiningrat - as the most prominent leaders of the independence movement — to proceed in the preparation of Indonesian independence'. Understandably, even though they have expected independence at long last, nevertheless at the time they were practically taken by sur- prise, particularly because they have not visualized a clear vision of what the future independence will be